2004
DOI: 10.1103/physrevb.70.014420
|View full text |Cite
|
Sign up to set email alerts
|

Energy functional dependence of exchange coupling and magnetic properties ofFeNbmultilayers

Abstract: We present an ab initio calculation of the exchange coupling for Fe/Nb multilayers using the self-consistent full-potential linearized augmented-plane wave (FLAPW) method. The exchange correlation potential has been treated in the local spin density approximation (LSDA) as well as generalized gradient approximation (GGA). We find that for the LSDA as well as the GGA the exchange coupling oscillates with a period of 6.0Å of Nb spacer thickness which is close to the experimental value in the preasymptotic region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…To calculate the total energies, the Brillouin zone summation was performed with a 32 × 32 × 1 k-point grid, the plane-wave energy cutoff was 400 eV, and the convergence criteria was less than 10 −3 meV. The sufficiently large number of k points and high accuracy of total energy calculation were needed to ensure that the estimated error in IEC was less than 10 −1 meV 42 43 .…”
Section: Methodsmentioning
confidence: 99%
“…To calculate the total energies, the Brillouin zone summation was performed with a 32 × 32 × 1 k-point grid, the plane-wave energy cutoff was 400 eV, and the convergence criteria was less than 10 −3 meV. The sufficiently large number of k points and high accuracy of total energy calculation were needed to ensure that the estimated error in IEC was less than 10 −1 meV 42 43 .…”
Section: Methodsmentioning
confidence: 99%
“…43 The observation of a reduced Fe moment in pseudomorphic Fe/Pt͑111͒ also correlates with the observation that in pseudomorphic Co films grown on W͑110͒ the tendency toward ferromagnetic ordering is strongly reduced while it is preserved in reconstructed films with partial misfit dislocations. 86 XMCD spectra have also been measured at the M 2,3 edges of Rh. They allow to conclude that the magnetic moments induced in the substrate are ferromagnetically aligned with those in the magnetic adlayer but a quantitative determination of the induced magnetization was impossible.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that antiferromagnetic (AF) coupling oscillates with period of about 0.8-1 nm. However, the first AF peak was observed near 6 monolayers of Nb(110) spacer instead of expected by ab-initio calculations 2 monolayers [9]. The above behaviour was explained by a relatively big difference in the lattice parameter of Fe and Nb (13%).…”
Section: Introductionmentioning
confidence: 70%